Pengimbuhan Minyak Jagung pada Pakan Meningkatkan Hirarki Folikuler dan Produktivitas Burung Puyuh (CORN OIL SUPLEMENTATION IN FEED INCREASE FOLICULLAR HIERARCHY AND PRODUCTIVITY OF JAPANESE QUAIL) - Pertiwi, Herinda; Mustofa, Imam; Hernawati, Tatik (Jurnal Veteriner, 2017)
The aim of this study was to measure the effect of corn oil in feed on estrogen hormone level in blood, hierarchy follicular performance and productivity of Japanese quail. Thirty female Japanese quail were housed in caged and fed ad libitum , the birds were randomly divided into three grouped namely: Po, P1 and the (P0) was fed with commercial feed without corn oil, whereas the first test treatment (P1) was fed with commercial feed mixture containing 3% corn oil, and the second test treatment (P2) was feed with commercial feed mixture containing 6% corn oil along the study. Every day the egg production was recorded. After eight weeks, blood samples were collected from jugular vein to isolate the serum. Then all samples were sacrificed to observe the hierarchy follicular performance. Based on this study it was found that 3% and 6 % corn oil supplementation on feed (P1 and P2) did not cause any significant changes in serum estrogen concentration, and productivity, but had significant changes on hierarchy follicular. This result show that hierarchy follicular increasing due to ovarian activity optimizing induced by polyunsaturated fatty acid (PUFA)by consumed corn oil. Thus, the suplementation of corn oil can be an alternative to increase egg productivity of quail farm. ABSTRAK Penelitian ini bertujuan untuk mengukur pengaruh pemberian minyak jagung dalam pakan terhadap kadar estrogen serum darah, hirarki folikular dan produktivitas burung puyuh. Sebanyak 30 ekor burung puyuh betina dibagi menjadi tiga perlakuan. Perlakuan kontrol diberi pakan komersial tanpa suplementasi minyak jagung, sedangkan perlakuan P1 dan P2 diberi pakan komersial dengan suplementasi minyak jagung sebanyak 3% dan 6%. Setiap hari dilakukan pencatatan terhadap produktivitas. Setelah delapan minggu, dilakukan koleksi sampel darah, kemudian semua burung puyuh dikorbankan nyawanya untuk mengamati hirarki folikular yang terbentuk. Pada P1 dan P2 tidak telihat perbedaan yang nyata terhadap peningkatan kadar estrogen serum darah dan produktivitas dibandingkan dengan P0, akan tetapi terlihat perbedaan nyata pada hirarki folikular yang terbentuk. Hasil ini menunjukkan bahwa peningkatan hirarki folikular yang terbentuk terjadi karena peningkatan kinerja ovarium dipicu oleh polyunsaturated fatty acid (PUFA) yang berasal konsumsi minyak jagung. Dengan demikian, suplementasi minyak jagung dapat dijadikan alternatif untuk meningkatkan produksi telur dalam peternakan burung puyuh.